Impact of improved glycaemic control on rates of hypoglycaemia in insulin dependent diabetes mellitus. Issue 2 (1st February 1998) - Davis, E A; Keating, B; Byrne, G C; Russell, M; Jones, T W
Abstract : Increased emphasis on strict glycaemic control of insulin dependent diabetes mellitus (IDDM) in young patients may be expected to cause increases in rates of significant hypoglycaemia. To evaluate whether this is the case for a large population based sample of IDDM children and adolescents rates of severe (coma, convulsion) and moderate (requiring assistance for treatment) hypoglycaemia were studied prospectively over a four year period.  A total of 709 patients were studied yielding 2027 patient years of data (mean (SD) age: 12.3 (4.4); range 0–18 years, duration IDDM: 4.9 (3.8) years). Details of hypoglycaemia were recorded at clinic visits every three months when glycated haemoglobin (HbA1c ) was also measured. Overall the incidence of severe hypoglycaemia was 7.8 and moderate was 15.4 episodes/100 patient years. Over the four years mean (SD) clinic HbA1c steadily fell from 10.2 (1.6)% in 1992 to 8.8 (1.5)% in 1995. In parallel with this there was a dramatic increase in the rate of hypoglycaemia, especially in the fourth year of the study, when severe hypoglycaemia increased from 4.8 to 15.6 episodes/100 patient years. This increase was particularly marked in younger children (<6 years) in whom severe hypoglycaemia increased from 14.9 to 42.1 episodes/100 patient years in 1995. It is concluded that attempts to achieve improved metabolic control must be accompanied by efforts to minimise the effects of significant hypoglycaemia, particularly in the younger age group.